KEMAMPUAN SISWA DALAM MENGINTERPRETASI GRAFIK MATERI PERSAMAAN GARIS LURUS MENGGUNAKAN GEOGEBRA - Tundung Memolo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Teachers are the most important source of learning while technology is the accelerator of learning in the classroom. Geogebra is one of the software used as an accelerator in the learning because of alignment as well as between algebra and visual representation of geometry. The use of Geogebra is done manipulation through the window provided so thatinteractive response can be captured quickly which can then be doneinterpretation. The advantages of using Geogebra is the ease of teachingand learning, and quick response in running the command so as to facilitate understanding a concept. This research method includes the type of applied research. The purpose of this study is to find out how much students ability in interpreting the graph of equations of straight line using Geogebra.Technique of collecting data of this research use written test documentation and interview. The results showed that 65% of students of grade VIII C SMPN 2 Kalibawang can reach values above 80.Keywords: garis, geogebra, interpretasi, persamaan, representasi